2001
DOI: 10.1159/000056001
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Hemorrhage in Neonates with Unrecognized Hemophilia A: A Persisting Problem

Abstract: Hemophilia is a rare disorder, and an uncommon cause of intracranial hemorrhage in neonates. We present 2 patients with hemophilia A, who presented with massive subdural hemorrhages on day 5 and day 4 postpartum. Both were taken urgently to surgery without a diagnosis of hemophilia being established. Neither patient had a family history of hemophilia, and both were born following difficult deliveries. The activated partial thromboplastin time (APTT) was normal in patient No. 1 (subsequent factor VIII level 10%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 10 publications
(16 reference statements)
0
17
0
1
Order By: Relevance
“…4 Individuals with ICH caused by bleeding disorders may require prophylactic replacement of coagulation factors. 72 …”
Section: Acutementioning
confidence: 99%
“…4 Individuals with ICH caused by bleeding disorders may require prophylactic replacement of coagulation factors. 72 …”
Section: Acutementioning
confidence: 99%
“…If normal vaginal delivery is the recommended routine mode of delivery for a pregnant haemophilia carrier, the screening for some potential hazards such as cephalo-pelvic disproportion may also be critical [12]. Moreover, it has been reported that extracranial haemorrhages frequently accompany ICH and a significant bleed in such a location should raise the suspicion of a concomitant ICH and underlying coagulopathy [43,44]. Even if somewhat non-specific (anaemia, pallor and apnea) and sometimes more unambiguous (seizures, lethargy and paresis), these recurrent symptoms must be recognized by caregivers in maternity hospitals as possibly because of ICH [12,33,39].…”
Section: Prevention and Treatment Of Neonatal Ichmentioning
confidence: 99%
“…Rapid stanching of bleeding may prevent progression to sensory and motor nerve compromise [19]. In addition, repletion of the missing clotting factor may prevent later spinal deformities when such bleeds occur in young children [20].…”
Section: Spinal Hematomamentioning
confidence: 99%